Development of an assessment method for hazardous substances value in automotive components for supporting green manufacturing - Yatna Yuwana Martawirya (ASEAN engineering journal)
The aim of this research is to develop an assessment method for hazardous substances value in automotive components for supporting green manufacturing. Basically, the green manufacturing focuses on reducing environmental risks and impacts of industrial activities through elimination of resource waste, pollution and use of material containing hazardous substances.In this research, the method will be used to assess hte hazardous substances contained in automotive components quantitatively.